General Geology and Economic Significance of the Lahor Granite and rocks of Southern Ophiolite Belt in Allai Kohistan area - Ashraf, Mohammad; Chaudhry, Muhammad Nawaz; Hussain, S. Shahid (Journal of Himalayan Earth Sciences, 1980)
Geological mapping of the toposheets (43 B/13 and F/1) carried out shows the following rock units in Besham-Kohistan and Allai areas: (1) Granitic rocks: Lahor granite and associated Shang granite gneiss and Mansehra (Susalgali) granite gneiss (2) Metarnorphics: Thakot group, Tanawal group, Salkhala series, Hazara type slates and dolomitic rocks and amphibolites (garnet amphibolite and normal ortho-amphibolites) (3) Jijal ultramafics: dunites/peridotites and pyroxenites. Economic mineral deposits found so far are magnetite (in skarns, hornblendites and ultramafics), sphalerite/galena (in skarns, veins and altered granite), chromite (in dunites/peridotites and pyroxenites) and molybdenite (in silicified skarns, altered granites and pegmatites). Anomalous values of Sn, W, Bi, Cd and Mn mineralization have been found in skarns, altered and silicified Lahor granite. The skarn type mineralization appears to be associated with the Precambrian Lahor granitic rocks which have intruded into the rocks equivalent to Salkhalas. This granite is. unconformably overlain by Hazara type slates and Abbottabad Formation (dolomitic). Two very important structural features have been noted in the area. They are, one older thrust separating Thakot group and associated Lahor granitic rucks and Tanawal group and associated Mansehra granite gneiss. The other very major thrust is the Main Mantle Thrust bringing ophiolite/amphibolite rocks onto Lahor granite, Thakot group, Tanawal group, Mansehra granite gneiss and the Salkhalas